2019
DOI: 10.1002/celc.201801727
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenative Anodic Cyanation Reaction of Phenols in Benzylic Positions

Abstract: The selective dehydrogenative electrochemical activation of benzylic positions by 1,1,1,3,3,3‐hexafluoropropan‐2‐ol (HFIP) and subsequent cyanation is presented for the first time. Herein, we report a sustainable, scalable, and metal‐free dehydrogenative benzylic cyanation protocol. Valuable 2‐phenylacetonitrile derivatives are accessible in the presence of a cyanide source and an electrolytically‐derived HFIP ether. The direct application of electricity enables a safe and environmentally benign chemical trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The use of fluoroalcohols (in particular 1,1,1,3,3,3‐hexafluoropropan‐2‐ol, HFIP) in electrosynthesis has major advantages, as it modulates the reactivity of intermediates, and has an exceptional solvent microhetero‐geneity . This has been recently demonstrated by conversion of electrogenerated HFIP ethers with nucleophiles towards diarylmethanes and 2‐phenylacetonitriles . We have also developed efficient electrochemical C−N, S−S, C−C, and N−N coupling reactions involving phenols, anilides, and dianilides as substrates…”
Section: Methodsmentioning
confidence: 98%
“…The use of fluoroalcohols (in particular 1,1,1,3,3,3‐hexafluoropropan‐2‐ol, HFIP) in electrosynthesis has major advantages, as it modulates the reactivity of intermediates, and has an exceptional solvent microhetero‐geneity . This has been recently demonstrated by conversion of electrogenerated HFIP ethers with nucleophiles towards diarylmethanes and 2‐phenylacetonitriles . We have also developed efficient electrochemical C−N, S−S, C−C, and N−N coupling reactions involving phenols, anilides, and dianilides as substrates…”
Section: Methodsmentioning
confidence: 98%
“…As shown in previous work, the HFIP moiety can be used as a leaving group . We wanted to show that this strategy can also be applied to arenes and therefore various functionalization reactions were conducted (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, we expanded the scope of the electroorganic synthesis of aryl HFIP ethers from our previous work to heterocycles. Key for these conversions is the amine‐HFIP electrolyte . In addition, the value of these intermediates was demonstrated in the activation within subsequent reactions.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that liberation of the benzylic cation is not necessary to achieve selective bond formation when stronger nucleophiles are used. [37] With cyanides, a direct substitution reaction is observed to yield 2-phenylacetonitriles, which represent important building blocks in organic synthesis. This structural feature is a precursor to many biologically active molecules such as 2phenylethylamines [45] or pharmaceuticals, such as the calcium ion channel blocker verapamil or the fungicide mandipropamid.…”
Section: Benzylic Anodic Cà H Functionalization With Hfip and Subsequmentioning
confidence: 99%
“…[35] Many more seminal applications of this powerful combination have been recently published and will be discussed within this review. [36][37][38][39][40]…”
Section: Introductionmentioning
confidence: 99%